Recent advances in Staphylococcus aureus infection: focus on vaccine development - Ansari, Shamshul; Jha, Rajesh Kumar; Mishra, Shyam Kumar; Tiwari, Birendra Raj; Asaad, Ahmed Morad (Infection and drug resistance, 2019)
normally colonizes the nasal cavity and pharynx. After breaching the normal habitat, the organism is able to cause a number of infections at any site of the body. The development of antibiotic resistance has created a global challenge for treating infections. Therefore, protection by vaccines may provide valuable measures. Currently, several vaccine candidates have been prepared which are either in preclinical phase or in early clinical phase, whereas several candidates have failed to show a protective efficacy in human subjects. Approaches have also been made in the development of monoclonal or polyclonal antibodies for passive immunization to protect from infections. Therefore, in this review we have summarized the findings of recently published scientific literature to make a concise report.